Risk of Cardiovascular Events Associated with Inhaled Corticosteroid Treatment in Patients with Chronic Obstructive Pulmonary Disease: A Meta-Analysis - Xia Jing; Yufeng Li; Jianying Xu (Canadian Respiratory Journal)
Background. The cardiovascular (CV) safety of inhaled corticosteroids (ICSs) in chronic obstructive pulmonary disease (COPD) is controversial because different studies have suggested that ICSs either increase or reduce the risk of CV events in COPD patients. In this meta-analysis, we assess the CV safety of ICS therapy in COPD. Methods. A meta-analysis of randomized, double-blind, parallel-group, placebo-controlled trials of ICS treatment for COPD that include at least 4 weeks of follow-up was performed. A random-effects model was used to evaluate the effects of ICS treatment on CV events. CV events were documented in each trial, and the relative risk (RR) and 95% confidence intervals (CIs) for ICSs were estimated. Results. Thirty-one trials were included in this meta-analysis. The risk of CV events was not different between ICS-treated and control groups (RR: 0.99; 95% CI: 0.93 to 1.06; P=0.801). In a subgroup analysis, there were no significant differences in CV events between an ICS combined with long-acting β2 agonist (LABA) (ICS + LABA) group and an LABA-only group (RR: 1.00; 95% CI: 0.90 to 1.10; P=0.930), as well as between a combination group (ICS + LABA) and a long-acting muscarinic antagonist (LAMA) combined with LABA (LAMA + LABA) group (RR: 0.78; 95% CI: 0.39 to 1.55; P=0.473). In addition, there was no difference in the risk of CV events between ICS treatment and control groups (RR: 0.99; 95% CI: 0.90 to 1.09; P=0.872). Conclusions. These results demonstrate that ICSs do not increase the risk of CV events in COPD patients.